Operational aspects of combat and service activity of the Interior Troops - Lavnichenko, О. V.; Hodlevskyi, S. O. (Honor and Law, 2019)
Justification of theoretical bases of definition of operational level of application of Interior Troops is given in article, as special military formation of the state.